PENANAMAN NILAI-NILAI KEAGAMAAN DAN MORAL PADA REMAJA PUTUS SEKOLAH OLEH ORANG TUA - Heni Indah Wati Sitorus; Gusti Budjang A; Imran Imran (Universitas Tanjungpura, 2019)
AbstractThis study entitled the cultivation of religious and moral values to dropping out of school adolescents by parents in Palo Belantian Hamlet Jelimpo Landak District. The problem in this study is how to cultivate religious and moral values to the adolescents by their parents. Based on problem for mulation, sub-problems are formulated namely on how to cultivate religious values in dropping out of school adolescents and how effective the cultivation of moral values in dropping out of school adolescents by parents. The form of this research is qualitative research with descriptive methods. Data collection techniques used in the study are guided observation, guided, interview and documentation. The results showed that the cultivation of religious values carried out by parents of drop out of school adolescents had not fully succeed, parents had not shown good example, lack of positive habituation, the advising and monitoring were good, parents advised dropping out of school adolescents and control their religious activities. Furthermore, the cultivation of moral values is quite good where parents cultivated moral values through habitual behavior such as politeness, honesty, tolerance and helpful.Keywords: Drop Out School Adolescents Teen, Parent, Value Implementation